Shyness and emotional vulnerability in language teaching: beliefs, emotions, and challenges of pre-service teachers - Dias, Pâmela Rabêlo (Universidade Federal de Viçosa, 2026)
Although shyness is a universal experience (Zimbardo, 1982), present in both childhood and adulthood and manifested either as a personality trait or situationally (Henderson; Zimbardo, 2001; Schmidt; Poole, 2020), Applied Linguistics (AL) still lacks studies focusing on the shyness of language teachers. Research has predominantly concentrated on learners’ shyness and its impact on oral production (Candido-Ribeiro, 2008; Santos; Barcelos, 2018; Bashosh et al., 2013), with few investigations, in Brazil or internationally, addressing the effects of shyness on teaching practice. Understood as a multidimensional psychological factor that generates discomfort and inhibition in social situations (Pilkonis, 1997; Carducci; Conkright, 2020), shyness may trigger emotions such as anxiety, fear, and embarrassment (Jones et al., 2014; Firouzi et al., 2024), affecting teachers’ well- being and professional performance, particularly with regard to communication, teacher competence, and interpersonal relationships (Etzold; Krüger, 2021). Given the demands of teaching, shy teachers may feel emotionally vulnerable, a condition inherent to the profession and central to understanding their experiences (Kelchtermans, 2012; Lasky, 2005; Song, 2016, 2022). Considering that beliefs and emotions are interrelated factors that influence teachers’ domain of action (Barcelos, 2004, 2015; Aragão, 2005, 2007, 2011), this study presents reflections on the relationship among shyness, emotional vulnerability, beliefs, and emotions of five pre-service language teachers at a federal university. This qualitative study (Richards, 2003; Creswell, 2013) was conducted through semi-structured questionnaires, written narratives, and semi-structured interviews. The findings indicate that shyness impacts language teachers’ emotional well-being, especially at the beginning of their teaching careers, when associated with limiting beliefs about themselves and about what it means to be a language teacher. Emotions perceived as uncomfortable, such as anxiety, fear, and shame (Jones et al., 2014), were identified, as well as positive emotions, such as empathy, gratitude, and passion. Participants reported feeling vulnerable when teaching, particularly due to exposure and a sense of professional inadequacy. Although dealing with vulnerability represents a challenge in the early stages of teaching, its effects tend to lessen over time and with professional experience. The implications of this study highlight the importance of valuing diverse teacher profiles and promoting the dissemination of the practical and emotional experiences of shy pre-service language teachers. Keywords: shyness; emotions; beliefs; emotional vulnerability; pre-service language teachers.

Embora a timidez seja uma experiência universal (Zimbardo, 1982), presente na infância e na vida adulta, manifestando-se como traço de personalidade ou de forma situacional (Henderson; Zimbardo, 2001; Schmidt; Poole, 2020), a Linguística Aplicada (LA) ainda carece de estudos voltados à timidez de professores de línguas. As pesquisas concentram-se majoritariamente na timidez de aprendizes e em sua produção oral (Candido-Ribeiro, 2008; Santos; Barcelos, 2018; Bashosh et al., 2013), sendo escassas, no Brasil e no cenário internacional, investigações sobre os impactos da timidez na prática docente. Compreendida como um fator psicológico multidimensional que provoca desconforto e inibição em situações sociais, (Pilkonis, 1997; Carducci; Conkright, 2020), a timidez pode desencadear emoções como ansiedade, medo e embaraço (Jones et al., 2014; Firouzi et al., 2024), afetando o bem-estar e o desempenho profissional docente, especialmente no que se refere à comunicação, à competência do professor e às relações interpessoais (Etzold; Krüger, 2021) Diante das exigências do ensino, professores tímidos podem sentir-se emocionalmente vulneráveis, condição inerente à docência e central para a compreensão de suas experiências (Kelchtermans, 2012; Lasky, 2005; Song, 2016, 2022). Considerando que as crenças e as emoções são fatores inter-relacionados que influenciam o domínio de ação docente (Barcelos, 2004, 2015; Aragão, 2005, 2007, 2011), este estudo apresenta reflexões sobre a relação entre timidez, vulnerabilidade emocional, crenças e emoções de cinco professores de línguas em formação inicial de uma universidade federal. Trata-se de uma pesquisa qualitativa (Richards, 2003; Creswell, 2013), conduzida por meio de questionários semiabertos, narrativas escritas e entrevistas semiestruturadas. Os resultados indicam que a timidez impacta o bem-estar emocional de professores de línguas, especialmente no início da docência, quando associada a crenças limitantes sobre si mesmos e sobre o que significa ser professor de línguas. Foram identificadas emoções consideradas desconfortáveis, como ansiedade, medo e vergonha (Jones et al., 2014), mas também emoções consideradas positivas, como empatia, gratidão e paixão. Os participantes relatam se sentir vulneráveis ao ensinar, sobretudo devido à exposição e ao senso de inadequação para desempenhar a profissão. Embora lidar com a vulnerabilidade represente um desafio nos momentos iniciais da docência, seus efeitos tendem a ser atenuados com o tempo e a experiência profissional. As implicações deste estudo destacam a importância de valorizar a diversidade de perfis docentes e de promover a disseminação das experiências práticas e emocionais vivenciadas por professores de línguas tímidos em formação inicial. Palavras-chave: timidez; emoções; crenças; vulnerabilidade emocional; professores de línguas em pré-serviço.
Timidez e vulnerabilidade emocional no ensino de línguas: crenças, emoções e desafios de professores em formação inicial
Keywords: Linguística aplicada; Timidez; Emoções; Crença e dúvida; Professores de línguas - Formação; Estudos Linguisticos